Designing Learning Communication Strategies Based on Basic Teaching Skills for Non-Education Students in Preparation for 'Kampus Mengajar' Batch 7 - Suprihatma, Suprihatma; Syaifudin, Ahmad Anif (UIN Sultan Aji Muhammad Idris Samarinda, 2024)
“Kampus Mengajar” Program Batch 7 focuses on teaching assistance in educational units. Through the implementation of the Kampus mengajar Program, it is expected that there will be a transfer of knowledge and skills between students and pupils in schools. Therefore, basic teaching skills must be mastered by students participating in the Kampus mengajar Program Batch 7. This study aims to identify and analyze the basic teaching skills of students from non-education majors participating in the Kampus mengajar Program Batch 7 in designing communication strategies based on basic teaching skills in preparing lessons. The method used in this study is a qualitative descriptive analysis method with data collection techniques of observation and in-depth interviews. The research subjects were selected using purposive sampling, totaling 7 students who are alumni of the Kampus mengajar Program Batch 7 from non-education majors, including Management, Accounting, Psychology, Communication Studies, Govermental Science, Law, and Computer science from Selamat Sri University. The results of the study show that non-education students participating in the Kampus mengajar Program Batch 7 experienced difficulties in several aspects such as delivering teaching, classroom management, adapting to the educational environment and teaching (culture shock), do not understanding teaching materials, having difficulty in preparing lessons. This condition is due to the fact that non-education students do not have a basic foundation in teaching skills. Therefore, this study offers several communication strategies that can be implemented in teaching, such as: mapping the potential of communicators, determining communication methods, and selecting communication media. These teaching communication strategies are expected to be an alternative for non-education students in preparing lessons.